Rancang Bangun Sistem Informasi Pengelolaan Surat dan Kearsipan pada Sekretariat Daerah Provinsi NTB Berbasis Web - Sumiati Sumiati; Sri Endang Anjarwani; Moh. Ali Albar (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2018)
The development in Information System of Mail and Archives Management at the Governor Office of West Nusa Tenggara is still supported by manual process off disposition, archiving, search, and mail recapitulation report process. The aim at developing this system is to help the managing and archiving mail so staff in subsection Expedition and Archives can manage mailing and archiving quickly and precisely. This system is developed based on programming language of HTML and PHP using framework CodeIgniter. It is examined through Black boxtechnique. The result is that every menu provided functions perfectly. The workflow of the information system has been suitable with the workflow of every work unit in the governor office of West Nusa Tenggara. Key words: Information system, Mail and Archives Management, Framework CodeIgniter, Mean Opinion Score.